Reducing workplace burnout: the relative benefits of cardiovascular and resistance exercise - Rachel Judith Bretland; Einar Baldvin Thorsteinsson (PeerJ, 2015)
Objectives. The global burden of burnout cost is in excess of $300 billion annually. Locally, just under half of working Australians experience high levels of occupational burnout. Consequently, burnout interventions are paramount to organisational productivity. Exercise has the potential to provide a multilevel and cost effective burnout intervention. The current study aims to extend the literature by comparing cardiovascular with resistance exercise to assess their relative effectiveness against well-being, perceived stress, and burnout.Design. Participants were 49 (36 females and 13 males) previously inactive volunteers ranging in age from 19 to 68 that completed a four week exercise program of either cardiovascular, resistance, or no exercise (control). Randomised control trial design was employed.Method. Participants were measured against the Subjective Exercise Experience Scale, the Perceived Stress Scale, and the Maslach Burnout Inventory.Results. After four weeks of exercise participants had greater positive well-being and personal accomplishment, and concomitantly less psychological distress, perceived stress, and emotional exhaustion. Cardiovascular exercise was found to increase well-being and decrease psychological distress, perceived stress, and emotional exhaustion. Resistance training was noticeably effective in increasing well-being and personal accomplishment and to reduce perceived stress. The present findings revealed large effect sizes suggesting that exercise may be an effective treatment for burnout. However, given a small sample size further research needs to be conducted.Conclusion. Exercise has potential to be an effective burnout intervention. Different types of exercise may assist employees in different ways. Organisations wishing to proactively reduce burnout can do so by encouraging their employees to access regular exercise programs.